A catalyst for producing gasoline by hydrocracking and its preparation method and application

By using ZSM-23 and modified Y-type molecular sieve as cracking centers and combining hydrocracking catalysts of Group VIB and Group VIII metals, the problems of low yield and low octane value in the catalytic diesel hydrogenation conversion and production of gasoline are solved, and high-quality gasoline is achieved efficiently.

CN117399063BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210777954.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-04
Publication Date
2025-04-01
Estimated Expiration
2042-07-04

AI Technical Summary

Technical Problem

In the process of catalyzing diesel hydrogenation conversion and production of gasoline, existing hydrocracking catalysts have common problems of low yield and low octane number.

Method used

A new hydrocracking catalyst is used, which consists of ZSM-23 molecular sieve and modified Y-type molecular sieve as cracking centers, combined with Group VIB and Group VIII metals as active metal components, and optimizes the specific surface area, pore volume and pore size distribution of the catalyst through specific preparation methods and process conditions to improve catalytic performance.

Benefits of technology

The high yield and high octane number of gasoline produced by catalytic diesel hydrocracking have been achieved, the quality of gasoline products has been improved, and the demand for high-quality gasoline by refining companies has been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
  • Figure 147198DEST_PATH_IMAGE004
    Figure 147198DEST_PATH_IMAGE004
Patent Text Reader

Abstract

This invention discloses a catalyst for the hydrocracking production of gasoline, its preparation method, and its application. The catalyst has the following properties: a specific surface area of ​​350–600 m² / g, a pore volume of 0.4–0.7 mL / g, with mesopores of 3–6 nm accounting for 35–60% of the total pore volume and mesopores of 6–15 nm accounting for 30–55% of the total pore volume. Based on the final catalyst weight, it contains 10 wt%–30 wt% active metal (calculated as oxides) and 70 wt%–90 wt% support. The catalyst preparation method includes the following steps: first, preparing ZSM-23 molecular sieve; then mixing and molding the prepared ZSM-23 molecular sieve, Y molecular sieve, amorphous silica-alumina, and binder, followed by drying and calcination to form a catalyst support; finally, introducing active metal onto the catalyst support, followed by drying and calcination to obtain the final catalyst. This catalyst is suitable for the catalytic hydrocracking of diesel to produce gasoline, exhibiting high gasoline yield and high gasoline octane number.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst for producing gasoline by hydrocracking, a preparation method and an application thereof, and in particular to a catalyst for producing high-quality gasoline by catalyzing diesel hydrocracking, a preparation method and an application thereof. Background Art

[0002] Catalytic cracking process is a major process technology for lightening heavy oil in the oil refining industry, and it occupies a relatively important position in domestic oil refining enterprises. As global oil becomes increasingly heavy, the processing capacity of FCC units is also constantly improving, producing a large amount of catalytic diesel with high sulfur, nitrogen, and aromatic content, low cetane number or cetane index, and extremely poor stability. In order to improve the utilization rate of oil resources, improve the overall quality level of gasoline and diesel fuels, achieve the goal of optimizing product blending and maximizing product value, and meet the growing domestic demand for clean fuels, it is necessary to find a suitable method to process it to meet the requirements of enterprise product delivery, adjust the gasoline and diesel product structure, and convert catalytic diesel into high-octane gasoline by hydrogenation. This is an effective way to alleviate the difficulties of catalytic diesel delivery in oil refining enterprises in recent years, and at the same time improve the benefits of enterprises. It has a good application prospect.

[0003] Hydrocracking catalyst is a bifunctional catalyst consisting of hydrogenation function and cracking function, in which the hydrogenation function is provided by hydrogenation active metal, which improves the hydrogenation performance of the catalyst and is beneficial to the saturation of aromatics. At present, the cracking center in most hydrocracking catalysts is provided by molecular sieves, and the key components that play a cracking role in such catalysts are usually Y and β molecular sieves.

[0004] β molecular sieve has insufficient aromatic saturation capacity, resulting in low gasoline octane number. EP20110834653 discloses a method for preparing a catalyst for hydroconversion of polycyclic aromatic hydrocarbons, wherein the catalyst carrier is composed of β molecular sieve and pseudo-boehmite, and the VIB group and VIII group active metal components are added by conventional methods, but the catalyst also has a strong saturation capacity for gasoline components, which is not conducive to the process of catalyzing diesel hydroconversion to produce high-octane gasoline.

[0005] CN109777714 discloses a method for catalytically converting diesel fuel into high-octane gasoline by hydrocracking. The method adopts a Y-type molecular sieve hydrocracking catalyst, which has the advantages of high ring-opening performance and high selective cracking performance for components rich in aromatics. The method can effectively control the depth of hydrogenation saturation of aromatics in the feedstock, convert part of the aromatics in the feedstock and enrich them in the naphtha fraction to produce high-octane gasoline blending components.

[0006] US2010116712 discloses a catalytic diesel hydroconversion method, which uses a conventional cracking catalyst. The crude oil is first pretreated and then contacted with the cracking catalyst to produce clean diesel and high-octane gasoline.

[0007] When the above catalyst is used in the catalytic diesel fuel production gasoline hydrocracking process, there are generally problems of low gasoline product yield and low octane number to varying degrees. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a catalyst for producing gasoline by hydrocracking, and a preparation method and application thereof. The catalyst is suitable for catalyzing diesel hydrocracking to produce gasoline, and has the characteristics of high gasoline yield and high gasoline octane number.

[0009] The present invention provides a catalyst for producing gasoline by hydrocracking, and the properties of the catalyst are as follows: the specific surface area is 350-600 m 2 / g, the pore volume is 0.4-0.7 mL / g, the catalyst has a pore size of 3-6 nm mesopores accounting for 35-60% of the total pore volume, and 6-15 nm mesopores accounting for 30-55% of the total pore volume; preferably, 3-6 nm mesopores account for 45-55% of the total pore volume, and 6-15 nm (excluding 6 nm) mesopores account for 35-45% of the total pore volume; based on the final catalyst weight, it contains 10wt%-30wt% of active metal in terms of oxide, and the remainder is carrier.

[0010] In the catalyst of the present invention, the active metal includes at least one of a VIB group metal and a VIII group metal. Based on the weight of the catalyst, the content of the VIB group metal is 10wt% to 20wt% in terms of oxide. The content of the VIII group metal is 2wt% to 10wt% in terms of oxide. The VIB group metal includes W and / or Mo; and the VIII group metal includes Co and / or Ni.

[0011] In the catalyst of the present invention, based on the carrier mass, the content of ZSM-23 molecular sieve is 3-15wt%, and the content of Y molecular sieve is 30-60wt%; the mesopore volume with a pore size of 3-6nm in the ZSM-23 molecular sieve accounts for 45-90% of the total pore volume of the molecular sieve, preferably 50-85%, and more preferably 55-81%.

[0012] In the catalyst of the present invention, the Y-type molecular sieve is a modified Y-type molecular sieve, and the Y-type molecular sieve SiO 2 / Al 2 O 3 The molar ratio is 10-25; preferably 15-20.

[0013] In the catalyst of the present invention, the properties of the ZSM-23 molecular sieve are as follows: the specific surface area is 300-430m 2 / g, pore volume is 0.31-0.5cm 3 / g, micropore specific surface area is 50-170m 2 / g, mesoporous specific surface area is 150-310m 2 / g; preferably, the specific surface area is 320-405m 2 / g, pore volume is 0.34-0.45cm 3 / g, micropore specific surface area is 80-140m 2 / g, mesopore specific surface area is 261-295m 2 / g.

[0014] In the catalyst of the present invention, the relative crystallinity of the ZSM-23 molecular sieve is 95-120%, and the relative crystallinity retention of the molecular sieve after hydrothermal treatment with 600° C. steam for 2 hours is 95-100%.

[0015] In the catalyst of the present invention, based on the mass of the carrier, the content of macroporous alumina is 20-60wt%, and the content of the binder is 10-30wt%.

[0016] In the catalyst of the present invention, the macroporous alumina has the following properties: pore volume of 0.6-1.2 mL / g, preferably 0.8-1.0 mL / g, specific surface area of ​​300-600 m 2 / g, preferably 400 to 500 m 2 / g.

[0017] In the catalyst of the present invention, the binder can be a commonly used binder in the art, preferably small-pore alumina. The small-pore alumina used has a pore volume of 0.3 to 0.5 mL / g and a specific surface area of ​​200 to 400 m 2 / g.

[0018] A method for preparing a catalyst for producing gasoline by hydrocracking: comprising the following steps: first preparing a ZSM-23 molecular sieve; then mixing and molding the prepared ZSM-23 molecular sieve, a Y molecular sieve, amorphous silicon aluminum and a binder, drying and calcining to prepare a catalyst carrier; finally introducing an active metal onto the catalyst carrier, drying and calcining to prepare a final catalyst. The preparation of the ZSM-23 molecular sieve refers to the preparation method of CN202210011767.9.

[0019] The preparation of the ZSM-23 molecular sieve comprises the following steps:

[0020] (1) preparing or selecting amorphous silicon dioxide;

[0021] (2) treating amorphous silica with an alkali;

[0022] (3) Preparation of ZSM-23 molecular sieve using alkali-treated amorphous silica as silicon source;

[0023] In step (1) of the above method, the amorphous silicon dioxide has a specific surface area of ​​600 to 1300 m 2 / g, preferably 700~1200 m 2 / g; pore volume is 0.6~1.3 cm 3 / g, preferably 0.7~1.2 cm 3 / g; the pore diameter is 1~15 nm, preferably 2~10 nm.

[0024] In step (1) of the above method, the amorphous silica preparation process is as follows: adding a silicon source to deionized water and dispersing it evenly, then adding a surfactant and stirring; adjusting the pH of the solution to 1-5, preferably 1.5-4, and heating it in a water bath for a period of time; filtering, washing, drying, and calcining to obtain amorphous mesoporous silica.

[0025] In the above method, during the preparation of amorphous silicon dioxide, the silicon source is an inorganic silicon source, preferably one or more of water glass, silica sol or white carbon black.

[0026] In the above method, during the preparation of amorphous silicon dioxide, the surfactant is one or more of hexadecyltrimethylammonium bromide / chloride and octadecyltrimethylammonium chloride / bromide.

[0027] In the above method, during the preparation of amorphous silicon dioxide, the silicon source is SiO 2 The molar ratio of the surfactant to the surfactant is 1: (0.02-0.3), preferably 1: (0.05-0.2).

[0028] In the above method, during the preparation of amorphous silicon dioxide, the silicon source is SiO 2 The molar ratio of the precipitate to deionized water is 1: (30-300), preferably 1: (50-220);

[0029] In the above method, during the preparation of the amorphous silica, the heating temperature is 30-80° C. and the heating time is 0.5-8 h; preferably, the heating temperature is 40-70° C. and the heating time is 3-6 h.

[0030] In step (2) of the above method, the alkali treatment is to add the amorphous silicon dioxide prepared in step (1) into an alkaline solution and heat and stir.

[0031] In the above method, the alkali treatment adopts inorganic alkali treatment, and the inorganic alkali is one or more of sodium hydroxide, potassium hydroxide or ammonia water.

[0032] In the above method, the alkali treatment heating and stirring time is 0.5~12 h, preferably 2~8 h; the heating temperature is 25~60°C, preferably 30~50°C.

[0033] In the above method, amorphous silicon dioxide is SiO 2 The molar ratio of the inorganic base is 0.04 to 0.15, preferably 0.05 to 0.13.

[0034] In step (3) of the above method, amorphous silica treated with alkali is used as a silicon source, and the silicon source is mixed with an aluminum source, an alkali source (MOH), a template (R), and water to form a gel, which is then crystallized, filtered, washed, dried, and calcined to obtain a HZSM-23 molecular sieve.

[0035] Preferably, the silicon source (in the form of SiO 2 Aluminum source (in Al 2 O 3 Alkali source (calculated as hydroxide): Template agent: H 2 O is 1: (0.003~0.03): (0.03~0.3): (0.05~2): (10~90); further preferably, the silicon source (in the form of SiO 2 Aluminum source (in Al 2 O 3 Alkali source (calculated as hydroxide): Template agent: H 2 The molar ratio of O is 1: (0.005~0.02): (0.03~0.15): (0.08~1.6): (20~70);

[0036] Preferably, the gel is crystallized at 150-200° C. for 24-96 hours, preferably at 170-180° C. for 36-72 hours, and then filtered, washed, dried and calcined to obtain the ZSM-23 molecular sieve.

[0037] In step (3) of the above method, the drying temperature is 80-120°C, the drying time is 4-12 h, the roasting temperature is 500-600°C, and the roasting time is 2-6 h.

[0038] In the preparation process of the ZSM-23 molecular sieve of the present invention, mesoporous amorphous silica is prepared with the assistance of a surfactant in the early stage, and it is used as a silicon source for the later synthesis of the ZSM-23 molecular sieve. The amorphous silica generated in the process has both a mesoporous structure and is not highly crystallized into a stable crystalline form. After being treated in a further low-concentration alkaline solution for a period of time, part of the -Si-O- bonds are opened, which is helpful for the subsequent generation of -Si-O-Al- bonds in the molecular sieve structure, but most of the mesoporous structure is retained. Under the action of a later microporous template agent, a microporous structure is generated in a suitable ZSM-23 molecular sieve synthesis system, and the mesoporous structure is further crystallized and stabilized, thereby preparing a micro-mesoporous composite ZSM-23 molecular sieve. The ZSM-23 molecular sieve synthesized by the method of the present invention has both the acidic properties of the microporous structure that can be adjusted, and the large pore characteristics of the mesoporous structure, high specific surface area and pore volume, high crystallinity, and strong thermal stability and hydrothermal stability.

[0039] In the preparation method of the catalyst according to the present invention, the molding can be conventionally selected as needed. The shape can be cylindrical bars, clover, etc. In the catalyst molding process, molding aids such as peptizing acid, extrusion aids, etc. can also be added. The peptizing agent can generally be inorganic acid and / or organic acid, and the extrusion aid is such as field sesbania powder. Conventional methods are used for drying and roasting. The drying is drying at a temperature of 80 to 120°C for 3 to 10 hours. The roasting is roasting at 400 to 600°C for 3 to 10 hours.

[0040] In the preparation method of the catalyst according to the present invention, the method for loading the active metal can adopt a conventional loading method, preferably an impregnation method, which can be a saturated impregnation, an excessive impregnation or a complex impregnation. Further, the impregnation method is to impregnate the support with a solution containing the active metal, dry it, and calcine it. The drying is drying at 100°C to 120°C for 1 to 12 hours. The calcination is calcining at 400°C to 600°C for 3 to 10 hours.

[0041] A method for producing gasoline by hydrocracking catalytic cracking diesel, wherein the catalytic cracking diesel is subjected to hydrocracking reaction under the action of the hydrocracking catalyst after being hydrorefined.

[0042] In the above method for producing gasoline, the properties of the catalytic cracking diesel are: density of 0.88 to 0.99 g / cm 3 , the dry point is 360-400°C, the aromatic content is 50-95wt%, the sulfur content of catalytic cracking diesel is 0.2-2wt%, and the nitrogen content is 500ppm-2000ppm.

[0043] In the above method for producing gasoline, the process conditions of the hydrofining reaction are: reaction temperature is 320-440°C, preferably 340-420°C; reaction pressure is 4.0-15.0MPa, preferably 6.0-12.0MPa; liquid hourly volume space velocity is 0.2-6.0h -1 , preferably 0.5~3.0h -1 ; The volume ratio of hydrogen to oil is 100 to 2000, preferably 500 to 1500.

[0044] In the above method for producing gasoline, the process conditions of the hydrocracking reaction are: reaction temperature is 340-440°C, preferably 360-430°C; reaction pressure is 4.0-15.0MPa, preferably 6.0-12.0MPa; liquid hourly volume space velocity is 0.2-6.0h -1 , preferably 0.5~3.0h -1 ; The volume ratio of hydrogen to oil is 100 to 2000, preferably 500 to 1500.

[0045] The ZSM-23 molecular sieve and the Y molecular sieve used in the catalyst of the present invention serve as the cracking center together, and have a double-mouth structure, which not only fully exerts their respective performance characteristics, but also enables the synergistic catalytic effect of the two molecular sieves. The Y molecular sieve is conducive to the diffusion of hydrocarbon molecules, can improve the preferential conversion ability of cyclic hydrocarbons, especially tricyclic aromatic hydrocarbons, and directionally saturates and breaks the aromatic ring in the middle of the tricyclic aromatic hydrocarbons. Secondly, through two-stage ring opening and cracking, the large molecular cycloalkylbenzene belonging to the diesel fraction is cracked into small molecular alkylbenzene and enriched in the gasoline fraction, so that the high-octane gasoline component in the product can be more.

[0046] The ZSM-23 molecular sieve of the present invention has a highly concentrated pore distribution characteristic of 3-6 nm, which can well adsorb and isomerize normal alkanes and small molecular alkylbenzenes in catalytic diesel, increase isomerization products, and further improve the octane number of gasoline products. The catalyst of the present invention is used for catalytic diesel hydrocracking to produce gasoline, and has the characteristics of high gasoline yield and gasoline octane number. DETAILED DESCRIPTION

[0047] In order to better illustrate the present invention, the present invention is further illustrated below in conjunction with examples and comparative examples. However, the scope of the present invention is not limited to the scope of these examples. Analysis method of the present invention: specific surface area and pore volume are determined by ASAP2405 low-temperature liquid nitrogen physical adsorption method, and the relative crystallinity of the molecular sieve is determined by X-ray powder diffraction (XRD). Among them, the sum of the heights of the diffraction peaks at 2θ of ~11.3 and 19.5-23° in the XRD spectrum of the microporous ZSM-23 molecular sieve is taken as 100% of the crystallinity, and the crystallinity of NaDZSM-23-1 prepared in comparative example 1 of the present invention is 100, and other samples are compared with it to obtain relative crystallinity. The phase silicon-aluminum molar ratio adopts a chemical method. In the present invention, wt% is the mass fraction and v% is the volume fraction.

[0048] In order to better illustrate the present invention, the following is further described in conjunction with examples and comparative examples. However, the scope of the present invention is not limited to the scope of these examples.

[0049] Example 1

[0050] (1) Preparation of mesoporous silicon source

[0051] Add 50 g of water glass (SiO 2 The mass fraction is 27%), and then octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 0.5 hours, wherein SiO 2 With C 18 The molar ratio of TMACl is 1:0.07; the solution pH is adjusted to 2 with hydrochloric acid, and then placed in a 50°C water bath and heated for 4 hours; after completion, the solution is filtered, washed, dried, and calcined at 550°C for 3 hours to obtain amorphous silica;

[0052] (2) Preparation of micro-mesoporous ZSM-23 molecular sieve:

[0053] a) Dissolve 0.35 g NaOH in 35 mL deionized water, add 3.7 g of the mesoporous silicon source prepared in (1), and stir in a 45°C water bath for 3 hours;

[0054] b) dissolving aluminum sulfate and isopropylamine (IPA) in the remaining water in sequence, and adding the silicon source dispersion obtained in a) thereto to prepare a silicon source having a total molar ratio of SiO 2 : Al in aluminum source 2 O 3 : NaOH : IPA : H 2The gel with O=1:0.01:0.08:1.0:50 was crystallized at 180℃ for 48 hours, filtered, washed, dried and calcined to obtain the product NaZSM-23-1. Its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. Its hydrothermal stability was measured after hydrothermal treatment with water vapor at 600℃ for 2 hours. The specific properties are shown in Table 1.

[0055] (3) Ammonium exchange

[0056] Weigh a certain amount of NaZSM-23-1 molecular sieve sample, place it in a 2 mol / L ammonium nitrate solution with a liquid-to-solid ratio of 10, and continue stirring in a water bath at 80-90 °C for 1 hour, then filter and wash. After repeating the above operation twice, place the sample in an oven at 80-100 °C for 8 hours and calcine it in an air atmosphere at 550 °C for 3 hours to obtain HZSM-23-1.

[0057] (4) Catalyst preparation

[0058] The carrier weight is 13% HZSM-23-1 molecular sieve, 37% Y molecular sieve (SiO 2 / Al 2 O 3 molar ratio of 20), 33% macroporous alumina (pore volume 0.9 mL / g, specific surface area 400 m 2 / g), and 17% small pore alumina (pore volume of 0.30 mL / g, specific surface area of ​​320 m 2 / g) and a binder composed of 10% by weight diluted nitric acid (HNO 3 / Small hole Al 2 O 3 The mixture was mixed and ground in a roller mill, water was added, and the mixture was rolled into a paste. The paste was extruded into strips. The strips were dried at 110° C. for 4 hours and then calcined at 550° C. for 4 hours to obtain carrier TC-1.

[0059] The carrier was impregnated with an impregnation solution containing tungsten and nickel at room temperature for 2 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain catalyst C-1. The corresponding catalyst properties are shown in Table 2.

[0060] Example 2

[0061] (1) Preparation of mesoporous silicon source

[0062] Add 50 g of water glass (SiO 2 The mass fraction is 27%), and the mixture is stirred and dispersed evenly, and then octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 0.5 hours, wherein SiO 2 With C18 The molar ratio of TMACl is 1:0.07; the solution pH is adjusted to 2 with hydrochloric acid, and then placed in a 50°C water bath and heated for 4 hours; after completion, the solution is filtered, washed, dried, and calcined at 550°C for 3 hours to obtain amorphous silica;

[0063] (2) Preparation of micro-mesoporous ZSM-23 molecular sieve:

[0064] a) Dissolve 0.42 g NaOH in 40 mL deionized water, add 3.7 g of the mesoporous silicon source prepared in (1), and stir in a 35°C water bath for 6 hours;

[0065] b) dissolving aluminum sulfate and isopropylamine (IPA) in the remaining water in sequence, and adding the silicon source dispersion obtained in a) thereto to prepare a silicon source having a molar ratio of SiO 2 : Al in aluminum source 2 O 3 : NaOH : IPA : H 2 The gel with O=1:0.01:0.10:1.0:50 was crystallized at 180℃ for 48 hours, filtered, washed, dried and calcined, and named as NaZSM-23-2. Its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. Its hydrothermal stability was measured after hydrothermal treatment with water vapor at 600℃ for 2 hours. The specific properties are shown in Table 1.

[0066] (3) Ammonium exchange

[0067] The preparation process of HZSM-23-2 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaZSM-23-2.

[0068] (4) Catalyst preparation

[0069] The carrier weight is 11% HZSM-23-2 molecular sieve, 39% Y molecular sieve (SiO 2 / Al 2 O 3 molar ratio of 20), 33% macroporous alumina (pore volume 0.9 mL / g, specific surface area 400 m 2 / g), and 17% small pore alumina (pore volume of 0.30 mL / g, specific surface area of ​​320 m 2 / g) and a binder composed of 10% by weight diluted nitric acid (HNO 3 / Small hole Al 2 O 3 The molar ratio of 0.26) was put into a roller mill for mixing and grinding, water was added, and the mixture was rolled into a paste, extruded into strips, and the extruded strips were dried at 110° C. for 4 hours and then calcined at 550° C. for 4 hours to obtain carrier TC-2.

[0070] The carrier was impregnated with an impregnation solution containing tungsten and nickel at room temperature for 2 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain catalyst C-2. The corresponding catalyst properties are shown in Table 2.

[0071] Example 3

[0072] (1) Preparation of mesoporous silicon source

[0073] Add 50 g of water glass (SiO 2 The mass fraction is 27%), and then octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 2 hours, wherein SiO 2 With C 18 The molar ratio of TMACl is 1:0.2; the solution pH is adjusted to 3 with hydrochloric acid, and then placed in a 50°C water bath for 4 hours; after completion, the solution is filtered, washed, dried, and calcined at 550°C for 3 hours to obtain amorphous silica;

[0074] (2) Preparation of micro-mesoporous ZSM-23 molecular sieve:

[0075] a) Dissolve 0.20 g NaOH in 35 mL deionized water, add 3.7 g of the mesoporous silicon source prepared in (1), and stir in a 45°C water bath for 3 hours;

[0076] b) dissolving aluminum sulfate, isopropylamine (IPA) and sodium hydroxide in the remaining water in sequence, and adding the silicon source dispersion obtained in a) thereto to prepare a silicon source having a molar ratio of SiO 2 : Al in aluminum source 2 O 3 : NaOH : IPA : H 2 The gel with O=1:0.01:0.08:1.0:50 was crystallized at 180℃ for 48 hours, filtered, washed, dried and calcined, and named as NaZSM-23-3. Its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. Its hydrothermal stability was measured after hydrothermal treatment with water vapor at 600℃ for 2 hours. The specific properties are shown in Table 1.

[0077] (3) Ammonium exchange

[0078] The preparation process of HZSM-23-3 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaZSM-23-3.

[0079] (4) Catalyst preparation

[0080] The carrier weight is 9% HZSM-23-3 molecular sieve, 41% Y molecular sieve (SiO 2 / Al 2 O 3 molar ratio of 20), 33% macroporous alumina (pore volume 0.9 mL / g, specific surface area 400 m 2 / g), and 17% small pore alumina (pore volume of 0.30 mL / g, specific surface area of ​​320 m 2 / g) and a binder composed of 10% by weight diluted nitric acid (HNO 3 / Small hole Al 2 O 3 The mixture was mixed and ground in a roller mill, water was added, and the mixture was rolled into a paste. The paste was extruded into strips. The extruded strips were dried at 110° C. for 4 hours and then calcined at 550° C. for 4 hours to obtain the carrier TC-3.

[0081] The carrier was impregnated with an impregnation solution containing tungsten and nickel at room temperature for 2 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain catalyst C-3. The corresponding catalyst properties are shown in Table 2.

[0082] Example 4

[0083] (1) Preparation of mesoporous silicon source

[0084] Add 50 g of water glass (SiO 2 The mass fraction is 27%), and then octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 2 hours, wherein SiO 2 With C 18 The molar ratio of TMACl is 1:0.2; after adjusting the pH of the solution to 4 with hydrochloric acid, the solution is placed in a 50°C water bath and heated for 4 hours; after completion, the solution is filtered, washed, dried, and calcined at 550°C for 3 hours to obtain amorphous silica;

[0085] (2) Preparation of micro-mesoporous ZSM-23 molecular sieve:

[0086] a) Dissolve 0.42 g NaOH in 40 mL deionized water, add 3.7 g of the mesoporous silicon source prepared in (1), and stir in a 40°C water bath for 3 hours;

[0087] b) dissolving aluminum sulfate and isopropylamine (IPA) in the remaining water in sequence, and adding the silicon source dispersion obtained in a) thereto to prepare a silicon source having a molar ratio of SiO 2 : Al in aluminum source 2 O 3 : NaOH : IPA : H 2The gel with O=1:0.005:0.10:1.0:50 was crystallized at 180℃ for 48 hours, filtered, washed, dried and calcined, and named as NaZSM-23-4. Its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. Its hydrothermal stability was measured after hydrothermal treatment with water vapor at 600℃ for 2 hours. The specific properties are shown in Table 1.

[0088] (3) Ammonium exchange

[0089] The preparation process of HZSM-23-4 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaZSM-23-4.

[0090] (4) Catalyst preparation

[0091] The carrier weight is 7% HZSM-23-4 molecular sieve, 43% Y molecular sieve (SiO 2 / Al 2 O 3 molar ratio of 20), 33% macroporous alumina (pore volume 0.9 mL / g, specific surface area 400 m 2 / g), and 17% small pore alumina (pore volume of 0.30 mL / g, specific surface area of ​​320 m 2 / g) and a binder composed of 10% by weight diluted nitric acid (HNO 3 / Small hole Al 2 O 3 The mixture was mixed and ground in a roller mill, water was added, and the mixture was rolled into a paste. The paste was extruded into strips. The extruded strips were dried at 110° C. for 4 hours and then calcined at 550° C. for 4 hours to obtain the carrier TC-4.

[0092] The carrier was impregnated with an impregnation solution containing tungsten and nickel at room temperature for 2 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain catalyst C-4. The corresponding catalyst properties are shown in Table 2.

[0093] Comparative Example 1 (refer to CN105540607A)

[0094] (1) Molecular sieve preparation

[0095] Under stirring at 35 °C, 0.51 g of pseudo-boehmite and 0.3 g of sodium hydroxide were added to 26 mL of deionized water. After the solution was homogenized, 0.3 g of isopropylamine was added, and then 21 g of white carbon black was added, and the mixture was homogenized again for 1 hour. 24.5 g of cereal starch was added, the mixture was heated to 90 °C, and stirred for aging for 6 hours. Finally, the obtained mixture was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, statically crystallized at 160 °C for 144 hours, taken out, cooled, filtered, and dried at 80 °C to obtain the original molecular sieve powder. After calcination at 500 °C for 12 hours in an air atmosphere, a micro-mesoporous composite NaDZSM-23-1 molecular sieve was obtained, and its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. After hydrothermal treatment with water vapor at 600 °C for 2 hours, its hydrothermal stability was measured. The specific properties are shown in Table 1.

[0096] (2) Ammonium exchange

[0097] The preparation process of H-DZSM-23-1 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaDZSM-23-1.

[0098] (3) Catalyst preparation

[0099] The preparation method of CC-1 catalyst is the same as that of Example 4 (4), except that the H-ZSM-23-1 molecular sieve is replaced by H-DZSM-23-1. The specific properties are shown in Table 2.

[0100] Comparative Example 2

[0101] (1) Preparation of mesoporous silicon source

[0102] Add 50 g of water glass (SiO 2 The mass fraction is 27%), and then octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 2 hours, wherein SiO 2 With C 18 The molar ratio of TMACl is 1:0.2; the solution pH is adjusted to 3 with hydrochloric acid, and then placed in a 50°C water bath and heated for 4 hours; after completion, the solution is filtered, washed, dried, and calcined at 550°C to obtain amorphous silica;

[0103] (2) a) Dissolve 0.70 g NaOH in 40 mL deionized water, add 3.7 g of the mesoporous silica source prepared in (1), and stir in a 45 °C water bath for 3 hours;

[0104] b) dissolving aluminum sulfate and isopropylamine (IPA) in the remaining water in sequence, and adding the silicon source dispersion obtained in a) thereto to prepare a silicon source having a molar ratio of SiO 2: Al in aluminum source 2 O 3 : NaOH : IPA : H 2 The gel with O=1:0.01:0.16:1.0:50 was crystallized at 180℃ for 48 hours, filtered, washed, dried and calcined to obtain sample NaDZSM-23-2. Its relative crystallinity, specific surface area, pore volume and pore size distribution were measured. Its hydrothermal stability was measured after hydrothermal treatment with water vapor at 600℃ for 2 hours. The specific properties are shown in Table 1.

[0105] (3) Ammonium exchange

[0106] The preparation process of H-DZSM-23-2 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaDZSM-23-2.

[0107] (4) Catalyst preparation

[0108] The preparation method of CC-2 catalyst is the same as that of Example 4 (4), except that the H-ZSM-23-1 molecular sieve is replaced by H-DZSM-23-2. The specific properties are shown in Table 2.

[0109] Comparative Example 3

[0110] (1) Molecular sieve sample preparation

[0111] Water glass, aluminum sulfate, isopropylamine (IPA), sodium hydroxide and water are mixed to prepare a total molar ratio of SiO in the silicon source. 2 : Al in aluminum source 2 O 3 : NaOH : IPA : H 2 The gel with O=1:0.01:0.08:1.0:50 was heated at 180°C for 72 hours, filtered, washed, dried and calcined to obtain a product named NaDZSM-23-3.

[0112] (2) Ammonium exchange

[0113] The preparation process of H-DZSM-23-3 is the same as that of Example 1 (3), except that the NaZSM-23-1 molecular sieve is replaced by NaDZSM-23-3.

[0114] (3) Catalyst preparation

[0115] The preparation method of CC-3 catalyst is the same as that of Example 1 (4), except that the H-ZSM-23-1 molecular sieve is replaced by H-DZSM-23-3. The specific properties are shown in Table 2.

[0116] Comparative Example 4

[0117] The Y molecular sieve (SiO 2 / Al 2 O 3 molar ratio of 20), 33% macroporous alumina (pore volume 0.9 mL / g, specific surface area 400 m 2 / g), and 17% small pore alumina (pore volume of 0.30 mL / g, specific surface area of ​​320 m 2 / g) and a binder composed of 10% by weight diluted nitric acid (HNO 3 / Small hole Al 2 O 3 The molar ratio of the aqueous solution to the aqueous solution was 0.26), water was added, the aqueous solution was rolled into a paste, and the aqueous solution was extruded. The extruded strips were dried at 110° C. for 4 hours and then calcined at 550° C. for 4 hours to obtain the carrier TC-4.

[0118] The carrier was impregnated with an impregnation solution containing tungsten and nickel at room temperature for 2 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain catalyst CC-4. The corresponding catalyst properties are shown in Table 2.

[0119] Table 1 Properties of molecular sieves

[0120]

[0121] a The products generated under this condition are mainly other molecular sieves, so this property cannot be analyzed;

[0122] dRelative crystallinity retention = crystallinity after hydrothermal treatment / relative crystallinity. Due to measurement errors, results greater than 100% are recorded as 100%.

[0123] Table 2 Physicochemical properties of catalysts

[0124]

[0125] The above catalyst was tested for activity evaluation. The test was conducted on a 200mL small hydrogenation unit, using a one-stage series hydrogenation reforming process. The properties of the raw oil used are shown in Table 4. The operating conditions are as follows: reaction pressure 6.5MPa, hydrogen-oil volume ratio 500:1, liquid hourly volume space velocity 1.0h -1 , <210℃ conversion rate 70wt%, refined oil nitrogen content 20ppm. The catalyst activity test results are shown in Table 4.

[0126] Table 3 Raw oil properties

[0127]

[0128] Table 4 Catalyst activity evaluation results

[0129]

[0130] It can be seen from the evaluation results of the catalysts in Table 4 that, compared with the comparative examples, the catalyst prepared by the present invention has a higher gasoline fraction yield and a higher octane number on the basis of higher activity.

Claims

1. A catalyst for producing gasoline by hydrocracking, characterized in that: The properties of the catalyst are as follows: the specific surface area is 350-600 m 2 / g, the pore volume is 0.4-0.7 mL / g, the mesopores with pore diameters of 3-6 nm in the catalyst account for 35-60% of the total pore volume, and the mesopores with pore diameters of 6-15 nm account for 30-55% of the total pore volume; based on the final catalyst weight, it contains 10wt%-30wt% of active metal in terms of oxide, and the remainder is carrier; Based on the carrier mass, the content of ZSM-23 molecular sieve is 3-15wt%, the content of Y molecular sieve is 30-60wt%, the content of macroporous alumina is 20-60wt%, and the content of binder is 10-30wt%; the sum of the contents of each component is 100%; The mesopore volume of the ZSM-23 molecular sieve with a pore size of 3 to 6 nm accounts for 45% to 90% of the total pore volume of the molecular sieve; The SiO2 / Al2O3 molar ratio of the Y molecular sieve is 10-25; the relative crystallinity of the ZSM-23 molecular sieve is 95-120%, and the relative crystallinity retention of the ZSM-23 molecular sieve after hydrothermal treatment with 600°C steam for 2 hours is 95-100%.

2. The catalyst according to claim 1, characterized in that: In the catalyst, mesopores with a pore size of 3-6 nm account for 45-55% of the total pore volume, and mesopores with a pore size of 6-15 nm account for 35-45% of the total pore volume.

3. The catalyst according to claim 1, characterized in that: The active metal includes at least one of a VIB group metal and a VIII group metal.

4. The catalyst according to claim 3, characterized in that: Based on the weight of the catalyst, the content of the VIB group metal is 10 wt% to 20 wt% in terms of oxide, and the content of the VIII group metal is 2 wt% to 10 wt% in terms of oxide.

5. The catalyst according to claim 3, characterized in that: The VIB group metal includes W and / or Mo; the VIII group metal includes Co and / or Ni.

6. The catalyst according to claim 1, characterized in that: The mesopore volume with a pore size of 3-6 nm in the ZSM-23 molecular sieve accounts for 50-85% of the total pore volume of the molecular sieve.

7. The catalyst according to claim 6, characterized in that: The mesopore volume with a pore size of 3-6 nm in the ZSM-23 molecular sieve accounts for 55-81% of the total pore volume of the molecular sieve.

8. The catalyst according to claim 1, characterized in that: The SiO2 / Al2O3 molar ratio of the Y molecular sieve is 15-20.

9. The catalyst according to claim 1, characterized in that: The properties of the macroporous alumina are as follows: pore volume of 0.6-1.2 mL / g, specific surface area of ​​300-600 m 2 / g.

10. The catalyst according to claim 9, characterized in that: The properties of the macroporous alumina are as follows: pore volume of 0.8-1.0 mL / g, specific surface area of ​​400-500 m 2 / g.

11. The catalyst according to claim 1, characterized in that: The adhesive is small-pore alumina, the pore volume of the small-pore alumina used is 0.3-0.5 mL / g, and the specific surface area is 200-400m 2 / g.

12. The method for preparing the catalyst according to any one of claims 1 to 11, characterized in that: The method comprises the following steps: firstly preparing a ZSM-23 molecular sieve; then mixing and molding the prepared ZSM-23 molecular sieve, a Y molecular sieve, macroporous alumina and a binder, drying and calcining the mixture to prepare a catalyst carrier; finally introducing an active metal onto the catalyst carrier, drying and calcining the mixture to prepare a final catalyst; the preparation of the ZSM-23 molecular sieve comprises the following steps: (1) preparing or selecting amorphous silicon dioxide; (2) treating amorphous silica with an alkali; (3) ZSM-23 molecular sieve was prepared using alkali-treated amorphous silica as the silicon source.

13. The method according to claim 12, characterized in that: The carrier is dried at a temperature of 80 to 120° C. for 3 to 10 hours, and the carrier is calcined at a temperature of 400 to 600° C. for 3 to 10 hours.

14. The method according to claim 12, characterized in that: After the active metal is introduced, the drying is performed at 100°C to 120°C for 1 to 12 hours, and the calcination is performed at 400°C to 600°C for 3 to 10 hours.

15. A method for producing gasoline by hydrocracking of catalytically cracked diesel, characterized in that: The catalytic cracking diesel is subjected to a hydrocracking reaction under the action of any catalyst of claims 1 to 11 after being hydrorefined.

16. The method according to claim 15, characterized in that: The properties of the catalytic cracking diesel are as follows: density is 0.88-0.99 g / cm 3 , the dry point is 360-400°C, the aromatic content is 50-95wt%, the sulfur content of catalytic cracking diesel is 0.2-2wt%, and the nitrogen content is 500ppm-2000ppm.

Citation Information

Patent Citations

  • Preparation method of ZSM-23 molecular sieve with mesopore-micropore hierarchical structure

    CN105540607A

  • ZSM-23 molecular sieve as well as preparation method and application thereof

    CN114715913A

  • Combination of mild hydrotreating and hydrocracking for making low sulfur diesel and high octane naphtha

    US20100116712A1

  • Composite molecular sieve-containing medium oil type hydrocracking catalyst, preparation method and application thereof

    CN103551186A

  • Hydrocracking catalyst and preparation method thereof

    CN106179462A